Smart cultural and political narratives in urban and periurban landscape - Chelidoni, Aikaterini; Moraitis, Konstantinos (Technical Annals, 2022)
Urban space constitutes in general the historical, cultural and politi-cal environment, the important ‘cultural landscape’, correlated not solely to ma-terial indices but, moreover, to immaterial, intangible mnemonic references. The possibility to present this multifaceted info-sense tissue to visitors is usual-ly assigned to guides personifying the description of the city, in a time and space restricted way, delimiting the volume of information and proposing a pre-confined number of guiding narratives only. Furthermore, these conventional guiding itineraries are usually directed to tourists, or to specialized didactic and presentational events; they are not offered to the immediate desire of knowledge or to the game-oriented tendency of the urban ‘flâneur’, of the urban stroller. Behind a conventional guiding tour, extended libraries, or galleries may be con-cealed, many hours of musical references; differentiated ‘ontologies’ of infor-mation, of semantic sequences which could be reorganized and reconnected again and again. Our effort presented in three different projects of urban landscape design, has to do with the correlation of this enormous quantity of interconnected in-formation with real space visiting itineraries, associated to virtual digital guid-ance as well. The scope of the projects presented is the same in all three pro-posals. It has to do with the importance of public urban and peri-urban space as a generator for social identity and cohesion. Considering that identities are basi-cally formed through socializing among members, as well as by exposing col-lective affiliations in public, the primary role of public space and the extended offer of cultural, historical and political information in such a process, is easily understood.